The War on Poverty's Experiment in Public Medicine: Community Health Centers and the Mortality of Older Americans - Bailey, Martha J.; Goodman-Bacon, Andrew (American Economic Review, 2015)
This paper uses the rollout of the first Community Health Centers (CHCs) to study the longer-term health effects of increasing access to primary care. Within ten years, CHCs are associated with a reduction in age-adjusted mortality rates of 2 percent among those 50 and older. The implied 7 to 13 percent decrease in one-year mortality risk among beneficiaries amounts to 20 to 40 percent of the 1966 poor/non-poor mortality gap for this age group. Large effects for those 65 and older suggest that increased access to primary care has longer-term benefits, even for populations with near universal health insurance. (JEL H75, I12, I13, I18, I32, I38, J14).